Salivary epigenetic biomarkers in head and neck squamous cell carcinomas. (March 2016) - Lim, Yenkai; Sun, Charles Xiaohang; Tran, Peter; Punyadeera, Chamindie
The early detection of head and neck squamous cell carcinoma (HNSCC) continues to be a challenge to the clinician. Saliva as a diagnostic medium carries significant advantages including its close proximity to the region of interest, ease of collection and noninvasive nature. While the identification of biomarkers continues to carry significant diagnostic and prognostic utility in HNSCC, epigenetic alterations present a novel opportunity to serve this purpose. With the developments of novel and innovative technologies, epigenetic alterations are now emerging as attractive candidates in HNSCC. As such, this review will focus on two commonly aberrant epigenetic alterations: DNA methylation and microRNA expression in HNSCC and their potential clinical utility. Identification and validation of these salivary epigenetic biomarkers would not only enable early diagnosis but will also facilitate in the clinical management.